Studies on Hypercoagulable State - Izak, G; Galewski, K; Eyal, Z (Thrombosis and Haemostasis, 1967)
The rate of disappearance of 131I-labelled, purified fibrinogen was estimated in 43 human subjects simultaneously with repeated determinations of various other constituents of the coagulation and fibrinolytic systems.A marked shortening of theT/2 of 131I-labelled fibrinogen was observed in patients with thromboembolic disease, as well as in some patients following extensive surgical procedures, in the absence of clinical signs of occlusive vascular lesions at the time of the study. In some of the latter patients thromboembolic episodes developed subsequently.The application of the procedures described here in the diagnosis of the so-called hypercoagulable state is discussed.